2017
DOI: 10.14419/ijans.v7i1.8524
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells: knowledge and attitude among health care providers in Qassim region, KSA

Abstract: Background: Health care providers as a trusted source of information for most patients should be able to provide counseling services to patients on the new concept of stem cells utilization, benefits and its practice implications.Objective: this study aims to assess the knowledge and attitude of health care providers in Qassim region regarding stem cells.Methods: Self-administered tools were utilized among 250 health care providers were chosen from five major hospitals in Qassim, including doctors, nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 15 publications
5
24
1
2
Order By: Relevance
“…According to our results, the knowledge level of the students is encouraging and suggests that they would be a trusted source of information, which would enable patients to make an informed decision regarding use of stem cells as a recent innovation in treatment. Our study showed a good knowledge level of 60.2% as compared to a similar study in KSA showing 31.2% good knowledge and 56% moderate knowledge among the respondents [11]. There was no association of stem cell awareness with gender, nationality, race, or year of study of the respondents in medical college corresponding to another study in Pakistan [12].…”
Section: Discussioncontrasting
confidence: 43%
“…According to our results, the knowledge level of the students is encouraging and suggests that they would be a trusted source of information, which would enable patients to make an informed decision regarding use of stem cells as a recent innovation in treatment. Our study showed a good knowledge level of 60.2% as compared to a similar study in KSA showing 31.2% good knowledge and 56% moderate knowledge among the respondents [11]. There was no association of stem cell awareness with gender, nationality, race, or year of study of the respondents in medical college corresponding to another study in Pakistan [12].…”
Section: Discussioncontrasting
confidence: 43%
“…In regenerative medicine, they have immense potential of promoting the repair response in diseased, dysfunctional or injured tissue ( MayoClinic, 2019 ). The knowledge and attitude of health care providers regarding stem cells is extremely important as they provide a reliable source of information to the patients which in turn improves the decision making power of patients regarding use of stem cells as a novel and innovative method of treatment ( Tork et al., 2017 ). Health care professionals are considered as the most trustworthy, dependable and reliable source of information about stem cells and umbilical cord blood banking by the members of public ( Dinç & Şahin, 2009 ; Perlow, 2006 ; Rucinski et al., 2010 ; Venugopal et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In regenerative medicine, they have immense potential of promoting the repair response in diseased, dysfunctional or injured tissue (MayoClinic 2019). The knowledge and attitude of health care providers regarding stem cells is extremely important as they provide a reliable source of information to the patients which in turn improves the decision making power of patients regarding use of stem cells as a novel and innovative method of treatment (Tork et al 2017). Health care professionals are considered as the most trustworthy, dependable and reliable source of information about stem cells and umbilical cord blood banking by the members of public (Dinç & Şahin 2009;Perlow 2006;Rucinski et al 2010;Venugopal et al 2016).…”
Section: Discussionmentioning
confidence: 99%